IMPORTANCIA DE SISTEMA DE INFORMACIÓN CONTABLE Importance of accounting information system - Sanchéz, Sesi Merari Baez; Fernández, Candelaria Guzmán; Magaña, Sergio Alfonso Tosca (IJRDO - Journal of Business Management, 2021)
This article is relevant to enrich the knowledge about the use and importance of the implementation of accounting information systems, which leads to having as a result providing a reliable service to clients. Its objective is to present general aspects of the acquisition and manipulation of accounting information systems, describing the doctrinal and regulatory variants applicable in the Mexican State. As a result, the employability of these systems determines and contributes to the management decision-making of the company or organization in an efficient and timely manner.